Agrofood know-how and skills. From use value to market value. The case of maize and cassava in the Cameroon - (:unkn) unknown (My University, 2001)
Africa displays a wide variety of local food products and processing skills that represent often unknown or underoalued, and until now under-exploited, assets. This study aims to better understand the mechanisms by 7.ohich some African products that initially were processed only in a domestic frameuJork have developed a marketable value. The authors analysed the processes underlying the selection and spatial dissemination ofsome market products and of the skiIls and know how they involve in South and West Cameroon. For instance, out of ten maize-based products created by specifie ethnie groups, four have been selected for marketing; for cassava products, the ratio is 6 to 11. The article considers the social process of creation and selection seen as the transition from a use value to an exchange value, and focuses more specifically on the symbolic value stage: this value may change as the products move away from their original community. Simultaneously and in relation with the changes in the value system, a transformation of the learning of skills may be observed. This rebounds back on the product value, and may account for certain differences in the spatial dissemination ofproducts (from a specifie territory for mintoumba to the national territory for foufou for example). Last, the migrations ofindividual bearers of these values and skills and also play an important role and need to be considered.
Keywords: African Research